UPAYA MENINGKATKAN HASIL BELAJAR IPA MATERI PERUBAHAN KENAMPAKAN PADA BUMI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Andriani, Suci; Pasaribu, Partogihon (Jurnal Mutiara Pendidikan Indonesia, 2018)
This study aims to determine whether the jigsaw type cooperative learning model can improve learning outcomes of fourth grade students at SD Negeri 023901 Binjai on material changes in appearance on earth. This research is Kemmis and Tagart class action research (CAR). The place of research taken by the author is SD Negeri 023901 Which is located at JL. Talam North Binjai District, Binjai City. The subjects of this study were 20th grade students of SD Negeri 023901, consisting of 11 men, 9 women. This study uses the Jigsaw Cooperative Learning Model. Based on the results of the study which became the conclusion of this study that the application of the jigsaw cooperative learning model in science learning can improve students learning outcomes on the material changes in appearance on earth fourth grade students of SD Negeri 023901 Binjai. This is evidenced by the increase in learning outcomes of class IV students from the pre-cycle with an average of 58,03, in the first cycle with an average of 70,1, and the second cycle with an average 0f 84,96. The level of classical completeness in the pre cycle was 35%, in the first cycle the level of classical completeness increased to 70% , and in the second cycle it was much higher compared to the pre cycle and the first cycle, which was 85%.